Reduced dopamine receptors and transporters but not synthesis capacity in normal aging adults: a meta-analysis - Karrer, Teresa M. (Neurobiol Aging, 2017)
Many theories of cognitive aging are based on evidence that dopamine (DA) declines with age. Here we performed a systematic meta-analysis of cross-sectional PET and SPECT studies on the average effects of age on distinct DA targets (receptors, transporters, or relevant enzymes) in healthy adults (N=95 studies including 2,611 subjects). Results revealed significant moderate to large, negative effects of age on DA transporters and receptors. Age had a significantly larger effect on D1- than D2-like receptors. In contrast, there was no significant effect of age on DA synthesis capacity. The average age reductions across the DA system were 3.7–14.0% per decade. A meta-regression found only DA target as a significant moderator of the age effect. This study precisely quantifies prior claims of reduced DA functionality with age. It also identifies presynaptic mechanisms (spared synthesis capacity and reduced DA transporters) that may partially account for previously unexplained phenomena whereby older adults appear to use dopaminergic resources effectively. Recommendations for future studies including minimum required samples sizes are provided.